2018
DOI: 10.1111/eth.12723
|View full text |Cite
|
Sign up to set email alerts
|

Female assessment of male functional fertility during mate choice in a promiscuous fish

Abstract: Sexual selection should favour females that can assess the functional fertility of available sexual partners and avoid mating with recently mated, sperm‐depleted males. Our current understanding of the sensory mechanism(s) underlying female assessment of males based on their functional fertility and avoidance of sperm‐depleted males is incomplete. Female Trinidadian guppies (Poecilia reticulata) are known to avoid mating with males that they had previously observed mating with other females. Here, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
(197 reference statements)
0
3
0
Order By: Relevance
“…These categories were calculated using the 25th, 50th, and 75th percentiles. Call rate values outside of this range are likely to present more extreme relationships than the ones presented here ◂ corroboree females to assess and choose males based on fertility (Scarponi and Godin 2018).…”
Section: Effect Of Age and Body Sizementioning
confidence: 61%
See 1 more Smart Citation
“…These categories were calculated using the 25th, 50th, and 75th percentiles. Call rate values outside of this range are likely to present more extreme relationships than the ones presented here ◂ corroboree females to assess and choose males based on fertility (Scarponi and Godin 2018).…”
Section: Effect Of Age and Body Sizementioning
confidence: 61%
“…Critically, intrinsic genetic quality may also be associated with superior sperm performance (Locatello et al 2006), with evidence in various taxa that males of higher genetic quality have increased sperm viability, motility, and longevity (Locatello et al 2006;Evans et al 2007); these are sperm traits known to influence fertilization success. Obtaining direct fertility benefits from mate choice is likely to be particularly important to females in polygynous mating systems, where males mate consecutively with multiple females, and highly successful males risk becoming sperm depleted (Scarponi and Godin 2018). In the P. corroboree mating system males are polygynous (Kelleher et al 2021a), and in the present study the most successful males would have mated with at least three females (estimated based on female average clutch size and the total number of eggs they received throughout the entire season).…”
Section: Effect Of Age and Body Sizementioning
confidence: 80%
“…For example, it has previously been shown that female guppies will avoid mating with males who have recently mated with another female (Scarponi et al 2015), a phenomenon which is seen in other species including cockroaches (Harris and Moore 2005), Drosophila (Loyau et al 2012), and in some circumstances, crayfish (Mellan et al 2014). Although female guppies can use chemical cues to assess a male's recent mating history (Scarponi & Godin 2018), such cues were not available to females in this experiment as they only had visual cues to assess the males. It therefore seems unlikely that male prior mating history would have affected female preferences observed in the current experiment.…”
Section: Discussionmentioning
confidence: 99%